Assessment of Laboratory Quality Management Systems in Primary Healthcare (The Review of Diabetic Studies, 2025)
Background: Good quality management systems (QMS) in clinical laboratories are a prerequisite for providing quality diagnostic services in primary healthcare settings, especially in resource-constrained settings.Objective: The main aim of this study was to evaluate the status of implementation of quality management systems in laboratories located in primary healthcare centers.Methods: This descriptive cross-sectional study was carried out between January and June 2025, covering 75 randomly selected laboratories located in primary healthcare centers. A validated checklist, which included 12 quality system essentials, was used for data collection, as recommended by ISO 15189:2012 and WHO SLIPTA (Stepwise Laboratory Quality Improvement Process Towards Accreditation). The checklist had a total of 258 points.Results: The mean overall compliance score was found to be 38.7% (100.2 ± 32.4 points out of 258). The mean score for the sections varied considerably, ranging from a maximum of 62.4% in Documents and Records to a minimum of 24.8%, 29.3%, and 26.7% in Facilities and Safety, Equipment Management, and Occurrence/Incident Management, respectively. Using the SLIPTA rating system equivalence, it was found that out of the total 75 laboratories, 68 scored 0 stars (0-105 points), 6 scored 1 star (106-145 points), and only 1 scored 2 stars (146-185 points), while no laboratory scored 3 stars and above. Major gaps were found in the areas of equipment calibration, where only 18.7% were found to be fully compliant, internal quality control practices, where only 31.0% were found to be compliant, and corrective action documentation, where only 22.7% were found to be compliant.Conclusion: Laboratory QMS implementation in primary healthcare centers continues to remain low, and most centers remain at the baseline level.